Policy on Prohibition of Advertising Traditional Health Services Conducted by Traditional Healers in Bali - Widnyana, I Made Adi; Winia, I Nyoman (Fakultas Dharma Duta UHN IGB Sugriwa Denpasar, 2024)
The existence of misleading and false advertisements for traditional health services from unqualified and incompetent sources has led the central and regional governments in Bali to issue a policy banning the advertisement of traditional health services by healers or practitioners of traditional medicine who are considered to lack professional competence. In its implementation, this policy still finds many traditional healers advertising in the field, so a study needs to be conducted to provide a good understanding for traditional healers and the community to avoid misleading traditional health advertisements. This research uses a normative method, with a case and legislative approach to examine the nature of the policy banning advertising for traditional healers and the impacts it has on traditional healers and the community as users of the traditional health advertising ban policy implemented in central and regional legal products. Overall, the policy banning the advertising of traditional health services by traditional healers in Bali aims to protect public health and safety, improve the quality of traditional health services, and maintain a balance between traditional and modern medicine in Bali. By limiting excessive promotion, the government hopes to encourage safe, responsible, and integrated traditional medicine practices within the modern healthcare system. This will provide greater benefits to the Balinese community in obtaining comprehensive and quality healthcare services. The impact of the advertising ban on Traditional Healers generally reduces the number of services provided to the community, while for the service-using community, this ban has a positive effect by providing information and education about traditional health services from expert and competent sources.